2005
DOI: 10.1093/carcin/bgi152
|View full text |Cite
|
Sign up to set email alerts
|

Multiple markers for melanoma progression regulated by DNA methylation: insights from transcriptomic studies

Abstract: The incidence of melanoma is increasing rapidly, with advanced lesions generally failing to respond to conventional chemotherapy. Here, we utilized DNA microarray-based gene expression profiling techniques to identify molecular determinants of melanoma progression within a unique panel of isogenic human melanoma cell lines. When a poorly tumorigenic cell line, derived from an early melanoma, was compared with two increasingly aggressive derivative cell lines, the expression of 66 genes was significantly change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 46 publications
4
90
0
1
Order By: Relevance
“…To date, three different studies have reported microarray-based screening following treatment of uveal or cutaneous melanoma cell lines with the DNA methylation inhibitor 5-aza-2 0 -deoxycytidine (5AzadC) (van der Velden et al, 2003;Gallagher et al, 2005;Muthusamy et al, 2006) to find new TSGs silenced by methylation. Van der Velden et al, (van der Velden et al, 2003) identified 19 genes, including TIMP3 (tissue inhibitor of metalloproteinase 3) and TYRP1 (tyrosinase related protein 1), that were differentially expressed between a demethylated derivative clone of a primary uveal melanoma cell line and its untreated control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, three different studies have reported microarray-based screening following treatment of uveal or cutaneous melanoma cell lines with the DNA methylation inhibitor 5-aza-2 0 -deoxycytidine (5AzadC) (van der Velden et al, 2003;Gallagher et al, 2005;Muthusamy et al, 2006) to find new TSGs silenced by methylation. Van der Velden et al, (van der Velden et al, 2003) identified 19 genes, including TIMP3 (tissue inhibitor of metalloproteinase 3) and TYRP1 (tyrosinase related protein 1), that were differentially expressed between a demethylated derivative clone of a primary uveal melanoma cell line and its untreated control.…”
Section: Discussionmentioning
confidence: 99%
“…Van der Velden et al, (van der Velden et al, 2003) identified 19 genes, including TIMP3 (tissue inhibitor of metalloproteinase 3) and TYRP1 (tyrosinase related protein 1), that were differentially expressed between a demethylated derivative clone of a primary uveal melanoma cell line and its untreated control. Gallagher et al, (2005) compared different highly tumorigenic derivative melanoma cell lines to their poorly tumorigenic parental cell lines (established from cutaneous superficial spreading melanomas). This group focused on TSPY, a Y chromosome specific gene normally expressed in the germ cells of the testis, which was hypermethylated in the derivative cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased TSPY expression occurs in testicular germ cell tumors 149 , as well as various types of somatic cancer, including melanoma 150 , prostate 151 and liver cancer 152 . Interestingly, while TSPY appears to exert a pro-oncogenic function, it has a homologue on the X chromosome, TSPX, which can be tumour suppressive 153 and protects from hepatitis B viral infection, a major risk for HCC 154 .…”
Section: B) Y Chromosomementioning
confidence: 99%
“…The downregulation of the TSPY gene in melanoma progression is caused by promoter hypermethylation. 32 A recent study showed that sudden infant death with dysgenesis of the testes syndrome (SIDDT, OMIM no. #608800) was due to a frameshift mutation in the TSPYL1 gene, and this resulted in truncation at codon 169 leading to the loss of a region with high homology to the NAP domain.…”
mentioning
confidence: 99%